Sustaining Empire : Venezuela's Trade with the United States during the Age of Revolutions, 1797-1828 - Pompeian, Edward P., 1983- (Book collections on Project MUSE., 2022)
A fascinating revisionist history, Sustaining Empire challenges long-standing assertions that this commerce served primarily as a vector for the one-way transmission of revolutionary, liberal ideas from the North to South Atlantic.